Perilaku Organisasi Dalam Pelayanan Publik (Library Research Di Indonesia) - Rizati, Leony; Wahidatunisa, Yolanda; Seviani, Dea; Aryani, Ririn Dwi; Lianti, Putri (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
Organizational behavior refers to the actions and interactions of individuals within an organization. Effective organizational behavior plays a crucial role in creating a positive impact, particularly in public institutions, by enhancing the quality of services provided to the public. One of the main obstacles to improving public services in government agencies is low compliance with established standards. Other factors, such as organizational structure, employee performance, organizational culture, and service systems, also affect public satisfaction. The purpose of this study is to analyze and describe organizational behavior in the context of public service delivery. This study employs a descriptive qualitative approach, utilizing library research as the primary method for data collection, followed by content analysis. The findings indicate that organizational behavior in public institutions is influenced by education, experience, work culture, leadership, training, and incentives. These factors collectively determine the quality of services provided. The research results suggest that the better the organizational behavior, the better the public services delivered. Therefore, organizations must optimize supporting factors to ensure continuous improvement in public service delivery.